(untitled) (Global Journal of Human-Social Science, 2018)
The study examined the socio-economic and paraphernalia effects and the causes of youth unemployment in Ogu Urban Town, and her sister towns in Ogu/Bolo Local Government Area (LGA), of Rivers State, Nigeria. The study indicated that youth unemployment has a lot of negative effects on the individual, family, economy and on the society. Youth unemployment leads to poverty, low productivity, and losses on the government in revenue generation; rural-urban migration, and illicit activities which increase insecurity, anti-social activities such as prostitution, political thuggery, violence, restiveness, petroleum bunkering and other social vices evident among the unemployed youths and this constitutes danger to the stability, growth, and development of the Local, State and Federal Government. Following on the research findings, we conclude that, problems of youth unemployment must be solved jointly by the three tiers of government, beginning with the unemployed and all stakeholders. Re-prioritization and revitalization of the agricultural sector (fishing predominantly for the riverine communities), acquisition of formal education, development of the needed infrastructures and building of industries be pursued vigorously which will significantly reduce unemployment in no small measure and poverty reduction as well as eradication of the menace of youth unemployment not only in Ogu/Bolo LGA but in the totality of Nigeria.